2022
DOI: 10.3389/fphys.2022.880815
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of lung aquaporins among other pathophysiological markers in acute (Cl2 gas) and chronic (carbon nanoparticles, cigarette smoke) respiratory toxicity mouse models

Abstract: Inhaled toxic chemicals and particulates are known to disrupt lung homeostasis causing pulmonary toxicity and tissue injury. However, biomarkers of such exposures and their underlying mechanisms are poorly understood, especially for emerging toxicants such as engineered nanoparticles and chemical threat agents such as chlorine gas (Cl2). Aquaporins (AQPs), commonly referred to as water channels, are known to play roles in lung homeostasis and pathophysiology. However, little is known on their regulation in tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…the increase of its level can lead to excessive secretion of mucin, which provides a good medium for virus reproduction, thus aggravating airway inflammation in patients with VALI ( 16); AQP5 is an important water transport channel in the airway and lung tissue. The decrease in its level can lead to too little mucus secretion, which increases the concentration of mucin and provides a good medium for virus reproduction (17). The results showed that the expression levels of MUC5AC and TLR4 in the VALIG were raised than those in the BCG, while the expression level of AQP5 in the VALIG was reduced to that in the BCG.…”
Section: Relative Expression Of Ampk and Pgc-1α Mrna In Rat Lung Tissuementioning
confidence: 96%
“…the increase of its level can lead to excessive secretion of mucin, which provides a good medium for virus reproduction, thus aggravating airway inflammation in patients with VALI ( 16); AQP5 is an important water transport channel in the airway and lung tissue. The decrease in its level can lead to too little mucus secretion, which increases the concentration of mucin and provides a good medium for virus reproduction (17). The results showed that the expression levels of MUC5AC and TLR4 in the VALIG were raised than those in the BCG, while the expression level of AQP5 in the VALIG was reduced to that in the BCG.…”
Section: Relative Expression Of Ampk and Pgc-1α Mrna In Rat Lung Tissuementioning
confidence: 96%
“…Numerous cellular mechanisms governing surfactant homeos impaired following exposure to CS and are reviewed in this sectio [131] BAL = bronchoalveolar lavage; CS = cigarette smoke; CSE = cigarette smoking extract.…”
Section: Molecular Mechanisms Leading To Cigarette-smoke-induced Modi...mentioning
confidence: 99%
“…As observed in humans, SP-A varied more heterogeneously after CS exposure, decreasing in three studies, increasing in three others and remaining unchanged in one. Only two studies [114,131] analyzed all four surfactant proteins. One [114] showed that CS caused an increase in the levels of SP-A and SP-D, whereas those of SP-B and SP-C were unchanged; the other [131] showed a CS-induced reduction for every SP.…”
Section: Cigarette Smoke Effect's On Composition and Abundance Of Sur...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lung homeostasis is maintained by critical mucosal proteins [26]. For example, surfactant proteins such as SP-A are required for the lubrication of the alveolar lining for normal lung function and the opsonization of microbes.…”
Section: Introductionmentioning
confidence: 99%